Characteristics of Activated Carbon Panels in Reducing CO, NO2, HC, Pb, and Noise - Darmanijati, Maria Roosa Srah; Pranoto, Pranoto; Ramelan, Ari Handono; Inayati, Inayati (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Increasing population growth has resulted in increased vehicle ownership and the need for parking facilities, including in basements. This study aimed to explore the efficacy of palm shell activated carbon panels in reducing CO, NO2, HC, Pb, and noise. The experiment was conducted in a 4 m x 3 m x 2.1 m room using three treatments: without installed activated carbon panels; with 1 cm x 20 cm x 20 cm activated carbon panels; and with 2 cm x 20 cm x 20 cm activated carbon panels. During the measurement, three motorcycles were turned on and kept in idle mode. The concentrations of CO, NO2, HC, ambient Pb, and noise were measured. The results showed that the activated carbon panels were able to reduce CO, NO2, Pb, HC, and noise. The highest performance was obtained for 2-cm thickness of activated carbon panels, with CO, NO2, HC, Pb, and noise decreasing to 824 µg/m3, 8.4 µg/m3, 4.4 µg/m3, 0.2 µg/m3, and 87.44 dB, respectively. Following the adsorption process, the carbon content and pore size of the activated carbon panels had changed from 68.32% to 90.95% and 0.17-3.652 µm to 0.34-5.56 µm respectively for testing with 2-cm thickness panels.